Environmental tobacco smoke exposure at home and smoking prevalence in the general Portuguese population--the INAsma study - Pereira, AM (2014)
BACKGROUND: We aimed to: 1) estimate the prevalence of exposure to environmental tobacco smoke (ETS) at home in the Portuguese population; 2) estimate tobacco smoking prevalence in Portugal; 3) identify social and personal characteristics associated with smoking or exposure to ETS. METHODS: Nationwide, cross-sectional, population-based telephone survey. Overall, 6003 individuals completed the interview. ETS exposure at home was defined as exposure to at least one current smoker at home. A smoker was defined as someone with 15 years or older, smoking at least 1 cigarette per day during a year; a current smoker (CS) smoked in the last month. RESULTS: Exposure to ETS at home was reported by 26.6% (95%CI 25.5-27.7) of the participants. Living in households with ≥4 persons (OR=2.31; 95%CI[1.81-2.96]), being a current smoker (OR=7.29; 95%CI[5.74-9.26]) or having current asthma (OR=2.06; 95%CI[1.45-2.94]) were factors positively associated with ETS exposure. When analyzed by gender, the effect of current asthma was only relevant to females. Currently 19.0% (95%CI 18.0-20.0) of the Portuguese population smokes tobacco and 17.2% (95%CI 16.2-18.2) are ex-smokers. CS prevalence is higher in males than females (26.5%versus 12.2%, p<0,001). The odds of being a CS were higher for males, the more educated, and those exposed to ETS at home. When analyzed by gender, school education only affected females. CONCLUSION: Exposure to ETS at home was higher than previously reported. Children/adolescents and asthma patients may have a higher risk of exposure. This report endorses a decreasing trend in the prevalence of tobacco smoking in Portuguese males, but a tendency to increase in females.